2021
DOI: 10.4103/ijn.ijn_386_19
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of Peritoneal Membrane Characteristics in Patients on Continuous Ambulatory Peritoneal Dialysis Using Standard Peritoneal Equilibration Test and Fast Peritoneal Equilibration Test

Abstract: Background: Evaluation of peritoneal membrane permeability in patients on continuous ambulatory peritoneal dialysis (CAPD) is crucial in prescribing treatment regimens. This study evaluated peritoneal membrane characteristics in patients on CAPD using standard peritoneal equilibration test (PET) and fast PET. Methods: A prospective observational longitudinal study included patients on CAPD with no symptoms of peritonitis for at least 4 weeks before the PET. Both, standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Moreover, previous studies reported that the Charlson score was related to LTI. Thus, we calculated this score using the medical history reported by the patient, cited in the medical record, or detected during the medical examination [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, previous studies reported that the Charlson score was related to LTI. Thus, we calculated this score using the medical history reported by the patient, cited in the medical record, or detected during the medical examination [ 12 ].…”
Section: Methodsmentioning
confidence: 99%